Community-Based Tourism Approach for Sustainable Development: A Study of the Lepcha Community, Kalimpong District, India - Das, Bijoy (Journal of Architectural/Planning Research and Studies (JARS), 2024)
Tourism is associated with the principles of Sustainable Development Goals (SDGs) in many ways because of its linkages with poverty alleviation, economic development, and environmental sustainability. The Community-Based Tourism (CBT) approach is one of the newly developed tourism types designed to resist mass tourism’s adverse environmental impacts with an aim for sustainable development. The present study was carried out to evaluate sustainable development using the CBT approach for the Lepcha community in the Kalimpong district of India. A self-designed, validated, semi-structured questionnaire survey was used to conduct the study with 250 participants selected through purposive sampling. The collected data were analyzed by both descriptive and inferential statistics in SPSS 20. Qualitative techniques also were used to verify the quantitative results of the study. The findings indicate that CBT and sustainability factors (economic, socio-cultural, and environmental) have a statistically significant positive correlation. So, the development of CBT is expected to bring economic sustainable development, followed by social-cultural and environmental development in the study area.